The Effect of Future Orientation and Financial Literacy on Family Retirement Planning Mediated by Saving Attitude - Muhammad Arfan Hajam (Institut Teknologi Sepuluh Nopember, 2020)
One of the ways to plan for a retirement plan is by setting a part of theincome or funds owned for future life purposes. Retirement planning forfamilies is carried out so that the finances remain stable when enteringretirement. This research aims to determine the effect of future orientationand financial literacy on family retirement planning is mediated by savingattitude. The sample in the research is families in the city of Surabaya.The data used in this research are the primary results of questionnaireswith 200 samples and data analysis techniques using SEM-PLS. Theresults of this research indicate future orientation and financial literacyhas a positive effect on family retirement planning and been mediated bysaving attitude in city of Surabaya.